Process of Drying Post-Harvest Hops (Humulus lupulus) for Small-Scale Producers Using a Novel Drying Rig: ENH1304/EP568, 1/2019 - Campbell, Sean M.; Pearson, Brian J. (EDIS, 2019)
Fresh horticultural goods often require drying post-harvest to preserve quality and allow for successful long-term storage of plant material. Given the influx of hops cultivation in the state of Florida, this 5-page publication will help Florida hops growers and hobby brewers to understand how to efficiently dry hops prior to storage. Written by Sean Campbell and Brian Pearson and published by the UF/IFAS Environmental Horticulture Department, January 2019. http://edis.ifas.ufl.edu/ep568